It´s all about keeping quiet – using focus group interviews to understand the everyday life of researchers in order to support their research - Wiklund, Gunilla; Voog, Hanna; Kjellberg, Sara (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
This paper describes how focus group interviews were used in a project on developing research support services. The object of the interviews was to understand the everyday lives of researchers and the obstacles they experience in their research process. Advantages and challenges of the method are discussed, e.g. the benefits of the interaction and the free form that the method allows for and the challenge not to interfere in the discussions and yet see to it that the discussions keep to the selected themes and keep on going.